ANALYSIS OF THE ROLE OF SOCIAL CAPITAL IN BMT (BAITUL MAAL WA TAMWIL) (Case Study BMT Incorporated with PUSKOPSYAH (Center for Sharia Coperative) Special District of Yogyakarta) - Widhia Restiawati (EKPI 16 UMY 326, 2016)
Social Capital is the capital that represents the features of social organization, namely trust, social networks, and norms. Microfinance plays a vital role in creating social capital. Social capital is the important capital to increase the performance of microfinance. This study aims to analyze the social capital in the form of trust, social networks, and norms in Islamic Microfinance, with case study in several BMTs incorporetaed with Puskopsyah DIY. In this study, sample of respondents are selected using purposive sampling, and used a qualitative method with descriptive statistical analysis. Based on the analysis, the result is BMT has succeeded a good record on doing the social capital and trust has the highest value compared to norms and social networks. Trust becomes the most social capital variables that is widely applied in BMT. While norms become the variable that have smallest value of social capital. Keywords: Social Capital, Trust, Social Networks, Norms, Baitul Maal Wa Tamwil (BMT).